Depletion of FoxP3+ Tregs improves control of larval Echinococcus multilocularis infection by promoting co‐stimulation and Th1/17 immunity. Issue 4 (16th June 2017) - Wang, Junhua; Müller, Stephan; Lin, Renyong; Siffert, Myriam; Vuitton, Dominique A.; Wen, Hao; Gottstein, Bruno
Abstract: Introduction: The growth potential of the tumor‐like Echinococcus multilocularis metacestode (causing alveolar echinococcosis, AE) is directly linked to the nature/function of the periparasitic host immune‐mediated processes. Previous studies had shown that regulatory T cells (Tregs) become gradually up‐regulated in the course of both chronic human and murine AE. Thus we now tackled the role of FoxP3 + Tregs and FoxP3 + ‐Treg‐regulated immune response in contributing to the control of this helminthic infection. Methods: The infection outcome in E. multilocularis ‐infected DEREG mice was measured upon determining parasite load (wet weight of parasitic metacestode tissue). Flow cytometry and qRT‐PCR were used to assess Treg, Th17‐, Th1‐, Th2‐type immune responses and antigen presenting cell activation. Results: We showed that E. multilocularis ‐infected DEREG‐mice treated with DT (as compared to infected control DEREG‐mice without DT application) exhibited a significantly lower parasite load, associated with a persisting capacity of co‐stimulation, and an increased Th1/Th17‐polarization. Conclusions: FoxP3 + Tregs appear as one of the key players in immune regulatory processes favoring (i) metacestode survival by inhibiting the maturation potential of co‐stimulatory activity and (ii) T cell exhaustion (suppressing Th1/Th17‐type immune responses). We showed as well that prospectively, targeting FoxP3 + Tregs could be an option to develop an immunotherapy against AE. Abstract : The growth potential of the tumor‐like Echinococcus multilocularis metacestode (causing alveolar echinococcosis, AE) is directly linked to the nature/function of the periparasitic host immune‐mediated processes. We showed now that E. multilocularis ‐infected DEREG‐mice treated with DT (as compared to infected control DEREG‐mice without DT application) exhibited a significantly lower parasite load, associated with a persisting capacity of DC‐maturation and co‐stimulation, and an increasing Th1/Th17‐polarization.